Deep learning-based crop health enhancement through early disease prediction - Venkata Santhosh Yakkala; Krishna Vamsi Nusimala; Badisa Gayathri; Sriya Kanamarlapudi; S. S. Aravinth; Ayodeji Olalekan Salau; S. Srithar (Cogent Food & Agriculture)
Manual disease detection methods currently in use are laborious, time-intensive, and heavily reliant on specialized knowledge. The urgent need to address these challenges motivates this study. The primary goal of this research is to develop a model capable of accurately distinguishing between healthy and diseased crop leaves. Additionally, the model aims to identify specific diseases affecting the crops if they are found to be diseased. Leveraging the power of machine learning algorithms, particularly Convolutional Neural Networks (CNNs) and ResNet-9 architecture, this research seeks to transform the process of detecting plant diseases. It focuses on analyzing diverse morphological features such as color, intensity, and dimensions in plant leaves to enable quick and accurate classification. By introducing AI-driven systems into agricultural practices, this study aims to revolutionize disease identification, prediction, and management. The overarching objective is to minimize crop losses and enhance agricultural productivity. In addition to highlighting the significance of machine learning techniques such as ResNet-9, this study emphasizes the importance of environmentally friendly biological control methods for regulating pests and diseases in agricultural settings. The adoption of Convolutional Neural Networks, specifically the ResNet-9 architecture, signifies a significant advancement in predicting plant diseases. This approach holds the promise of vastly improving the accuracy and efficiency of disease forecasting within the agricultural domain.